Public Opinion Sentiment Analysis on the Indonesian Music Royalty Polemic in the Public Space using the RoBERTa Transformer: A Case Study of YouTube Comments - Irman, Dede; Surya, Dhika; Laksitohika, Grida Saktian (International Journal of Humanities, Law, and Politics, 2025)
This study aims to analyze public perception of the music royalty controversy in Indonesia through YouTube comments. The development of digital technology has made YouTube a public space where discourse on cultural and policy issues, such as music royalty payments in the commercial space, is openly expressed. This study uses a quantitative approach with sentiment analysis based on the RoBERTa (Robustly Optimized BERT Pretraining Approach) model adapted for Indonesian, namely the Indonesian RoBERTa Base Sentiment Classifier. Primary data was obtained from comments on a YouTube video titled "Royalty Polemic, Cafes Afraid to Play Indonesian Songs" published by KompasTV. The analysis results show that negative sentiment dominates public conversation with 9,595 comments, far exceeding neutral (3,395) and positive (2,548) sentiment. This dominance of negative sentiment reflects strong public resistance to the royalty payment policy, which is perceived as an additional burden for business actors. Further qualitative analysis reveals that negative sentiment generally contains criticism and concern, while neutral sentiment is descriptive, and positive sentiment, although minor, indicates support for musicians' copyright protection. This study concludes that YouTube serves as a spontaneous and broad reflection of public opinion, and the use of the RoBERTa model proved effective in capturing the rich nuances of informal language in comments. This research contributes to filling a gap in the literature, which tends to focus on legal and economic aspects, by providing a digital data-based understanding of public responses to the issue of music royalties.